The Effectivity of “Sinau Aksara Jawa (Sadewa)” Module in Improving Aksara Jawa Reading and Writing Skills (Universitas Negeri Semarang, 2022)
According to the observation results of Javanese Language subject matter on Aksara Jawa learning materials in 3rd grade of SDN Plalangan 03, it was found that most of students have an inability to focus on the subject materials when learning Aksara Jawa that were taught by the teacher. Students are less motivated in learning aksara Jawa. The usage of learning media and resources to convey the learning material still less varied so that reading and writing skills are lessoptimum. The purpose of this research is the effectivity of Sinau Aksara Jawa (Sadewa) module in improving Aksara Jawa’s reading and writing skills. The samples of this research are 3rd grade students of SDN Plalangan 03 and SDN Pakintelan 03. The sampling that used in this research is simple random sampling. The research data were collected through a test of Aksara Jawa’s reading and writing skills. The data were analyzed through mean difference test in SPSS application that called paired sample t-test. The results of this research revealed that there is significant difference between the pretest and posttest results of reading and writing test skills using Sinau Aksara Jawa (Sadewa) module. According to the results, the working hypothesis (Ha) were accepted which means the Sinau Aksara Jawa (Sadewa) module is effective in improving the reading and writing skills of 3rd grade students.